The effectiveness of wound caring technique with polyhexamethylene biguanide and dialkyl carbamoyl chloride to healing process duration of diabetic foot ulcer patient - Armi Armi; Dewi Fitriani; Mila Sartika; Yana Setiawan (Faculty of Nursing Universitas Padjadjaran, 2023)
Background: Antimicrobial dressing on moist-based wound care is a successful wound care technique, especially for diabetes mellitus wounds. The moisture on wound can be made by closed wound care to reach a standard moisture in various wounds. The antimicrobial dressing type that can increase the wound healing is Polyhexamethylene biguanide (PHMB) and Dialkyl carbamoyl chloride (DACC). Polyhexamethylene biguanide can accelerate the tissue granulation and reduce the risk of infection. Dialkyl carbamoyl chloride is a part of moist wound healing with strong hydrophobic threat so the bacteria will be lifted and accelerate the wound healing process. The aim of this research is to analyze the effect of healing technique using Polyhexamethylene biguanide and Dialkyl carbamoyl chloride wound healing process on diabetic foot ulcer patients. Methods: This research was quasi-experimental with 129 respondents. The instruments were Bates Jensen’s observation sheet and data were processed by double linear regression. Results: It was obtained an average difference between the duration of the wound healing process between PHMB and DACC therapy with a p-value of 0.0005. Conclusion: The use of this type of DACC dressing is more effective against the duration of the healing process of diabetic foot ulcers because of the time needed for DACC to work on killing bacteria in-vitro in 30 minutes compared to other dressing.